Dam Risk Identification Method Based on EAHP-EWM-TOPSIS - ZHAN Mingqiang; CHEN Bo; TIAN Jufei; HU Zelin; PAN Xinmei (Renmin Zhujiang)
To address the uncertainty and fuzziness of dam risk indicators, this paper proposes a dam risk identification model based on the EAHP-EWM-TOPSIS game combination model.This is to determine the subjective and objective weights of risk evaluation indicators by extension analytic hierarchy process and entropy weight method respectively.Meanwhile, the game theory is introduced to determine the optimal combination weight, and a weighted standardized decision matrix is constructed.Then, the TOPSIS method is employed to calculate the relative proximity between each risk factor and the ideal solution as the basis for ranking risk factors to identify the main risk sources of dams.The engineering example shows that the main risk factors affecting the safe service of the dams are dam seepage and cross-bank seepage, with the relative proximity of 0.712 7 and 0.855 2 respectively.The identified main risk factors are consistent with the actual engineering situation, which verifies the model effectiveness.The differentiation degree of this model is more obvious than other models, providing an effective basis for dam reinforcement and risk management.